Role of Soil Nutrient Status in Microbial Activity and Disease - Gretchen F. Sassenrath; Christopher R. Little; Xiaomao Lin (Kansas Agricultural Experiment Station Research Reports, 2025)
The soil supports many living organisms, in addition to plants. Bacteria and fungi are critical components of the soil ecosystem and play fundamental roles in the biochemistry of the soil. This study explores the interdependency of the soil microbiome and soil nutrient status.
Keywords: charcoal rot; soil nutrient levels; soybeans